2021
DOI: 10.1155/2021/7284042
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Trypanosoma congolense and Trypanosoma vivax in Lira District, Uganda

Abstract: Trypanosomes are the causative agents of animal African trypanosomiasis (AAT) and human African trypanosomiasis (HAT), the former affecting domestic animals prevalent in Sub-Saharan Africa. The main species causing AAT in cattle are T. congolense, T. vivax, and T. b. brucei. Northern Uganda has been politically unstable with no form of vector control in place. The return of displaced inhabitants led to the restocking of cattle from AAT endemic areas. It was thus important to estimate the burden of trypanosomia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
(40 reference statements)
0
7
1
Order By: Relevance
“…The higher proportion of T. congolense (80.55%) in all PAs in the current study was inconsistent with the report by Katabazi et al 24 who reported 81.8% T. congolense from the total trypanososomes detected. Similarly, highest prevalence rate of T. congolense (59.6%) was indicated by Megersa et al 28 This high prevalence of T. Congolense infection in cattle may be because of high serodemes (serological variation) of T. congolense as compared to other Trypanosoma species and development of immune response improvement against T. vivax by infected animals (Sinshaw et al).…”
Section: Entomological Findingcontrasting
confidence: 99%
See 1 more Smart Citation
“…The higher proportion of T. congolense (80.55%) in all PAs in the current study was inconsistent with the report by Katabazi et al 24 who reported 81.8% T. congolense from the total trypanososomes detected. Similarly, highest prevalence rate of T. congolense (59.6%) was indicated by Megersa et al 28 This high prevalence of T. Congolense infection in cattle may be because of high serodemes (serological variation) of T. congolense as compared to other Trypanosoma species and development of immune response improvement against T. vivax by infected animals (Sinshaw et al).…”
Section: Entomological Findingcontrasting
confidence: 99%
“…There was a statistically significant difference between both sexes (P<0.05). Katabazi et al,24 from Lira District of Uganda and 4.17% by Kivali et al,25 from Western Kenya. Similarly, Gerem et al26 reported the overall prevalence of 4.5% of camel trypanosomiasis from Asayita and Dubti area of Afar region.…”
mentioning
confidence: 96%
“…T. congolense is one of the most prevalent and pathogenic African trypanosome species in the ‘tsetse belt’ [ 1 , 31 33 ]. Its development in the tsetse fly is essential for transmission and successful establishment in the mammalian host.…”
Section: Discussionmentioning
confidence: 99%
“…Among the species mentioned, T. congolense has been considered the second most virulent and the most pathogenic species in cattle leading to AAT ( Katabazi et al, 2020 ). After infection, the parasite develops extracellularly and interacts with circulating erythrocytes and vital organs of the infected host thereby causing profound damage at the adhesion sites.…”
Section: Introductionmentioning
confidence: 99%